Pola Pertumbuhan dan Identifikasi Genetik Turbo setosus Gmelin, 1791 [Turbinidae, Gastropoda] - Dandi Saleky; Febriyani Eka Supriyatin; Muhammad Dailami (Jurnal Kelautan Tropis, 2020)
Morphological dan genetic identification is an essential part of biology and ecological study. Environmental degradation, physical and chemical facto in water, and utilization of gastropod by society will give impact in distribution pattern, population size, morphology and genetic characteristic of the snail. This research aims to analyze the growth pattern and molecular aspect of Turbo setosus. The variable that examined is total weight and length, and cytochrome oxidase subunit one gene sequence. The growth factor of T. setosus is negative allometric, which means weight growth is slower than the length growth. The total length of cytochrome oxidase subunit 1 of these samples were 650 base pairs. Based on the DNA barcoding analysis, the sequence is 96.92% identic with the sequence of T. setosus in GenBank. The phylogenetic tree was reconstructed with neighbour-joining methods and 1000 replication bootstrap, show the clade grouping based on the similarity and genetic distance of the species. The sequence data is vital for species identification fast and accurately.    Identifikasi morfologi dan genetik menjadi bagian penting dari setiap studi biologi maupun ekologi, degradasi lingkungan, faktor fisik-kimia lingkungan dan pemanfaatan gastropoda secara terus menerus akan mempengaruhi penyebaran, penurunan populasi, karakteristik morfologi dan juga karakter molekuler spesies. Penelitian ini bertujuan untuk menganalisis pola pertumbuhan dan karakter molekuler Turbo setosus. Variabel yang diukur adalah berat total dan panjang total serta identifikasi molekuler dengan menggunakan gen sitokrom oksidase I. Pola pertumbuhan T. setosus adalah allometrik negatif yang berarti pertambahan berat lebih lambat dari pertambahan panjang. Hasil identifikasi dengan DNA barcoding diperoleh spesies T. setosus dengan panjang sekuen DNA 650 bp. Rekonstruksi filogenetik dengan metode Neighbor-Joining boostrap 1000x memperlihatkan pengelompokan sekuen berdasarkan kimiripan dan jarak genetik antar spesies. penting dalam identifikasi spesies secara cepat, tepat dan akurat.